Determination of Coil Inductances Cylindrical Iron Nucleus - Azeddine Mazouz; Djemai Hidjazi; Aziz Chaghi (IAES Indonesian Section, 2014)
The paper describes the investigation and development of a structure and performance characteristics of a coil iron nucleus cylindrical (C.I.N.C). The coil iron nucleus cylindrical is a nonlinear electro radio in which the moving of the nucleus in a sense or in other causes change in inductance and can reach extreme values at the superposition of nucleus and coil centers. The variation of the inductance and the degree of freedom of movement of the nucleus can lead to a device with electromechanical conversion The aim of this paper is the determination and visualization of self inductance and mutual of the (C.I.N.C) based on geometric dimensions and the displacement of the nucleus.